Systematic Literature Review: Integrating Islamic Education in English Language Teaching - Djamdjuri, Dewi Suriyani; Gatot, Masitowati; Yusiyaka, Rahmi Alendra; Sahril, Mohamad; Mufaridah, Fitrotul; Pratama, Muhamad Ilsan (UNIB Press, 2023)
Islamic literature, history, and customs are common subjects and resources incorporated into effective English teaching in Islamic nations since they are relevant to the culture. The aims of this study are to explore the integration of Islamic education in English language teaching as well as how teachers can teach English by instilling Islamic values to develop good character in their students. This study involves a systematic literature review (SLR). An SLR requires significant searching across multiple article databases as well as additional journal databases such as Google Scholar to supplement and expand the main database. The next step involved obtaining and locating additional supplies manually. This step entailed reading pieces of literature for which the only information provided was the author, source, or title. The study reveals that understanding culture and society can help integrate religious teaching into ELT. It is critical to understand the cultural and theological context. Teachers who are knowledgeable of Islamic customs, values, and sensitivities should teach them in the classroom. Moreover, to provide students with a well-rounded education, Islamic principles and ethics can be integrated into English language classes. Teachers can explore issues and subjects that are in line with Islamic principles while encouraging critical thinking, creativity, and intercultural understanding.